Reverse Mortgages: Understanding the Basics - Michael S. Gutter; Selena Garrison; Brent Litchfield; Lisa Leslie (EDIS)
FCS3305, a 7-page fact sheet by Michael S. Gutter, Selena Garrison, Brent Litchfield, and Lisa Leslie, describes this type of tax-free loan that can be used to help fund retirement — requirements, cost considerations, alternatives, types of reverse mortgages, fees and interest, limitations, distribution types, and types of unscrupulous practices. Includes references. Published by the UF Department of Family Youth and Community Sciences, October 2009.